2014
DOI: 10.1038/eye.2014.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of head elevation on intraocular pressure in healthy subjects: raising bed head vs using multiple pillows

Abstract: Purpose To evaluate the effects of different methods of head elevation on intraocular pressure (IOP) in healthy young subjects. Methods Twenty-four healthy young Korean subjects were included in this prospective observational study. The IOP measurements were taken with the subjects in the sitting position and in the supine positions with the head flat and 301 up using two different methods: (1) raising the bed head and (2) using multiple pillows. IOP was measured using Tonopen AVIA in both eyes 10 min after as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
3
14
0
2
Order By: Relevance
“…The 109 eye clinical study indicated zero bias error between the CATS and GAT prisms. Low correlation coefficients are common in clinical IOP studies due to the multiple variables in measurement error [ 20 23 ]. The assumption made in statistical analysis examining correlation is that the biomechanical error relationships are linear when in fact there is evidence that they may be non-linear which may add to a lower correlation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 109 eye clinical study indicated zero bias error between the CATS and GAT prisms. Low correlation coefficients are common in clinical IOP studies due to the multiple variables in measurement error [ 20 23 ]. The assumption made in statistical analysis examining correlation is that the biomechanical error relationships are linear when in fact there is evidence that they may be non-linear which may add to a lower correlation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The supine position measurement adds significantly more error to the applanation IOP compared to the upright position. Several studies have examined the clinical differences in IOP measurement between upright and supine positions and have shown either the same or increased IOP when supine [ 20 22 ]. The critical difference in these studies and ours is found in the modulated control and of the intracameral pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The head elevation of 30° from the supine position was also shown to reduce nocturnal IOP significantly in normal subjects, but the same study did not find an IOP reduction when 2 pillows were used to elevate the head a similar amount ( P =0.061 OD, P =0.089 OS). 53 A 20% head only up position utilizing only a wedge pillow in OAG and normal patients found an almost significant reduction in nocturnal IOP in either group (95% confidence interval 0.99–2.04). 54 While a 3.2 mmHg IOP reduction overnight may not seem clinically significant, a millimeter of IOP reduction has been shown to reduce the risk of progression in OAG patients 10% 55 and one-third of our life is spent in a sleeping position.…”
Section: Discussionmentioning
confidence: 94%